Holocene benthic foraminiferal and ostracod assemblages in a paleo-hydrothermal vent system of Campi Flegrei (Campania, South Italy) - Aiello, G.; Barra, D.; Parisi, R.; Isaia, R.; Marturano, A. (Palaeontologia Electronica, 2018)
The succession of the Late Quaternary La Starza terrace, located within the Campi Flegrei caldera, on the Tyrrhenian side of southern Italy, represents a wellknown example of deposition under the combined influence of bathymetric and physico- chemical variations due to volcanic activities. One hundred and seven samples collected in six outcrops and some tunnel excavation fronts, with an age between 12 and 4 k.y.a, comprise both barren and fossiliferous sediments. The latter contain siliceous and/or calcareous microfossil remains, including benthic foraminiferal and ostracod assemblages indicative of a marine paleodepth ranging from the upper infralittoral to the upper circalittoral zone, with phases of intense environmental stress typical of a hydrothermal system. A detailed reconstruction of the Holocene paleoenvironmental evolution of the succession is presented. The majority of foraminiferal and ostracod species is illustrated and brief taxonomic and ecological notes are given for each of them.